1994
DOI: 10.1046/j.1471-4159.1994.63020584.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Cerebral and Cerebellar Mitochondria Produce Free Radicals when Exposed to Elevated Ca2+ and Na+: Implications for Neurodegeneration

Abstract: The evidence is compelling that free radicals, plus increases in free cytosolic Ca2+ and Na+, figure prominently in neuronal death after exposure to glutamate and dicarboxylic excitotoxins such as NMDA and kainate. However, neither the source of these radicals nor the direct connection between Ca2+ mobilization and radical production has been well defined. Electron paramagnetic resonance studies reported here indicate that intact mitochondria isolated from adult rat cerebral cortex and cerebellum generate extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
212
0
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(223 citation statements)
references
References 33 publications
6
212
0
5
Order By: Relevance
“…Where indicated, 5 mM succinate or 5 mM ␣-ketoglutarate A were included into the medium. The sequence of additions was as follows: mitochondria (0.1-0.125 mg/ml) were added into the incubation medium and incubated for 2 min, then phosphorylation was inhibited with 1. activity is stimulated by Ca 2ϩ and ADP may perhaps account for previous findings that mitochondrial ROS production was increased by Ca 2ϩ (Dykens, 1994;Kowaltowski et al, 1995Kowaltowski et al, , 1996Kowaltowski et al, , 1998a, Ca 2ϩ in the presence of rotenone and succinate , and by ADP (Barja, 1999). The results presented in the accompanying report by Tretter and Adam-Vizi (2004) demonstrate that Ca 2ϩ activated ROS production by isolated KGDHC both in the presence and in the absence of pyridine nucleotides.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Where indicated, 5 mM succinate or 5 mM ␣-ketoglutarate A were included into the medium. The sequence of additions was as follows: mitochondria (0.1-0.125 mg/ml) were added into the incubation medium and incubated for 2 min, then phosphorylation was inhibited with 1. activity is stimulated by Ca 2ϩ and ADP may perhaps account for previous findings that mitochondrial ROS production was increased by Ca 2ϩ (Dykens, 1994;Kowaltowski et al, 1995Kowaltowski et al, , 1996Kowaltowski et al, , 1998a, Ca 2ϩ in the presence of rotenone and succinate , and by ADP (Barja, 1999). The results presented in the accompanying report by Tretter and Adam-Vizi (2004) demonstrate that Ca 2ϩ activated ROS production by isolated KGDHC both in the presence and in the absence of pyridine nucleotides.…”
Section: Discussionmentioning
confidence: 71%
“…The finding that H 2 O 2 production is frequently reported as being almost absent in the presence of succinate and rotenone (Barja, 1999;Liu et al, 2002) is intriguing because the intramitochondrial NADPH/NADP ϩ ratio under such conditions is high. Stimulatory effects of ADP (Barja, 1999) and Ca 2ϩ (Dykens, 1994;Kowaltowski et al, 1995Kowaltowski et al, , 1996Kowaltowski et al, , 1998a on mitochondrial ROS production are also puzzling because both Ca 2ϩ uptake/retention and ADPinduced oxidative phosphorylation dissipate energy and would be expected to decrease the level of reduction of complex I and hence the ROS production. It also appears that the stimulatory effect of the complex I inhibitor rotenone on ROS production that possibly originates from a site within complex I is species and tissue dependent; ROS stimulation by rotenone varies from ϳ300% in guinea pig to 0% in horse heart submitochondrial particles (Herrero and Barja, 2000) and in whole intact rat heart mitochondria (Chen et al, 2003) to inhibition of ROS production in mouse kidney mitochondria (Kwong and Sohal, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of oxygen during reperfusion induces the uncoupling of the electron flow from the mitochondria electron transport chain, causing the accumulation of free radicals. During hypoxic-ischemic injury, Ca 2+ is accumulated in the cytosol (see above) and enters into mitochondria, which results in the production of mitochondrial free radicals (Hasegawa et al, 1993;Dykens, 1994; Dugan et al, 1995;Giulivi et al, 1995;Piantodosi and Zhang, 1996). Excess Ca 2+ in the mitochondria interrupts the electron transport chain and collapses the mitochondrial membrane potential (Zhang et al, 1990;Rego et al, 2000).…”
Section: Production Of Reactive Oxygen Species In Mitochondriamentioning
confidence: 99%
“…14 Overstimulation of ionotropic glutamate receptors (iGluR), namely N-methyl-D-aspartate (NMDA) receptors, provokes pathophysiological increases in intracellular Ca 2ϩ and consequently leads to the activation of several overlapping Ca 2ϩ -dependent processes, such as the generation of mitochondrial reactive oxygen species and loss of cellular viability. [15][16][17][18][19][20] DOM has been shown to be 8 to 10 times more potent than kainic acid in rodents, producing a similar reproducible pattern of behavioral toxicity culminating in seizures. 8,21,22 Studies conducted in rats, mice, and cynomolgus monkeys have shown a consistent pattern of DOM-induced damage to the hippocampal pyramidal neurons, as well as to the thalamic, amygdalar, entorhinal, cortical, and septal neurons after DOM administration (0.22 to 4.4 mg/kg i.p.).…”
mentioning
confidence: 99%